The Influence of Work Discipline and Communication Management on the Performance of Employees in the Computer Stitching Central Division at PT Adis Dimension Footwear, Tangerang Regency - Ramadhan, Dini Anggraeni; Yulandari, Sri; Umam, Akhmad Hairul (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The purpose of this study was to determine how much influence work discipline and communication management simultaneously have on employee performance in the Computer Stitching Central section at PT. Adis Dimension Footwear, Tangerang Regency.This study uses a quantitative descriptive method. The population in this study were all employees of the Computer Stitching Central section at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 61 respondents.The results of this study indicate that (1) partially, work discipline significantly influences employee performance in the Computer Stitching Central section at PT. Adis Dimension Footwear, Tangerang Regency (2) Partially, communication managmenet significantly influences employee performance in the Computer Stitching Central section at PT. Adis Dimension Footwear, Tangerang Regency (3) Simultaneously, work discipline and communication management significantly influence employee performance in the Computer Stitching Central section at PT. Adis Dimension Footwear Tangerang RegencyBased on the results of the study, it can be concluded that the variables of work discipline and communication management, both partially and simultaneously, have a significant influence on employee performance in the Computer Stitching Central section at PT. Adis Dimension Footwear Tangerang Regency.